41‐1: Invited Paper: Active Matrix Mini‐LED Backlights for 1000PPI VR LCD. Issue 1 (29th May 2019) - Wu, Yang-En; Lee, Ming-Hsien; Lin, Yi-Cheng; Kuo, Chienhung; Lin, Yung-Hsu; Huang, Wei-Ming
Abstract : An active matrix mini‐LED backlight for 1000PPI VR LCD is demonstrated using LTPS backplane. With the local dimming function and switchable VR modes, visual experience of VR LCD is further enhanced. By reducing the IR drop, the backlight is capable to output 130, 000 nits.